Birth weight, early childhood growth and lung function in middle to early old age: 1946 British birth cohort. Issue 10 (16th July 2015) - Cai, Yutong; Shaheen, Seif O; Hardy, Rebecca; Kuh, Diana; Hansell, Anna L
Abstract : Background: Findings from previous studies investigating the relationship between birth weight and adult lung function have been inconsistent, and data on birth weight and adult lung function decline are lacking. Few studies have investigated the relation between early childhood growth and adult lung function. Methods: FEV1 and FVC were measured at ages 43 years, 53 years and 60–64 years in the 1946 British birth cohort study. Multiple linear regression models were fitted to study associations with birth weight and weight gain at age 0–2 years. Multilevel models assessed how associations changed with age, with FEV1 and FVC as repeated outcomes. Results: 3276 and 3249 participants were included in FEV1 and FVC analyses, respectively. In women, there was a decreasing association between birth weight and FVC with age. From the multilevel model, for every 1 kg higher birth weight, FVC was higher on average by 66.3 mL (95% CI 0.5 to 132) at 43 years, but significance was lost at 53 years and 60–64 years. Similar associations were seen with FEV1, but linear change (decline) from age 43 years lost statistical significance after full adjustment. In men, associations with birth weight were null in multilevel models. Higher early life weight gain was associated with higher FEV1 at age 43 years in men and women combined but not in each sex. Conclusions: Birth weight is positively associated with adult lung function in middle age, particularly in women, but the association diminishes with age, potentially due to accumulating environmental influences over the life course.